Policy mechanisms to decarbonize cement production: through the lens of California - Pablo Busch; Alyson Kim; Colin W Murphy; Sabbie A Miller (Environmental Research: Infrastructure and Sustainability)
Cement production is a large global industry that is a significant source of carbon dioxide (CO _2 ) emissions, from both energy-derived and process-derived sources. Cement is crucial for concrete, the most widely used building material. There are growing pushes for policies that encourage cement production with net-zero greenhouse gas emissions. Effective policymaking requires understanding the barriers to adoption of emission-lowering strategies, the existing policy framework, and potential regulations for emission reduction. In this work, we examine these parameters within the context of California’s recent net-zero emissions cement bill, Senate Bill 596, focusing on six key decarbonization strategies. We highlight key barriers for these mechanisms and policy strategies that could support a transition to lower emissions. Some crucial actions are public procurement and replacement of prescriptive design codes with performance-based approaches to create a marketplace for novel cements; refine models and conduct pilot projects to study novel cement or mixture performance, durability and costs; and increase awareness with education and communication campaigns directed at stakeholders. Policy actions can be adopted and adapted in other regions that will design net-zero emissions policies.